Control Plane Issues in the 4WARD Network Virtualization Architecture - Bless, Roland; Werle, Christoph (Electronic Communications of the EASST, 2009)
Network virtualization technologies offer a lot of opportunities and advantages but create also new issues that need to be solved. In this paper, we discuss control mechanisms, interfaces, and protocols required in order to allow for dynamic setup of virtual networks. Finally, we describe some runtime aspects by examining control interfaces and signaling protocols necessary for the management of virtual networks.